Semi-individualized homeopathy add-on versus usual care only for premenstrual disorders: a randomized, controlled feasibility study - Klein-Laansma, Christien; Hagens, Cornelia von (Journal of alternative & complementary medicine, 2018)
Premenstrual syndrome and premenstrual dysphoric disorder (PMS/PMDD) bother a substantial number of women. Homeopathy seems a promising treatment, but it needs investigation using reliable study designs. The feasibility of organizing an international randomized pragmatic trial on a homeopathic add-on treatment (usual care [UC] + HT) compared with UC alone was evaluated.
Gesehen am 31.10.2019